A Broken Idyll: Post-Pastoralism in the Works of George Crumb - Kristina KNOWLES (E-REA)
Pastoral is one of the oldest and most enduring musical topics, yet most scholarship exploring it in music ends with the beginning of the twentieth century. This paper seeks to examine the expression of the pastoral in the musical output of post-modern composer, George Crumb. In doing so, I argue that the concept of post-pastoralism put forth by Terry Gifford may provide a valuable lens through which to understand musical expressions of the pastoral in the post-modern era. The article ends with a close reading of George Crumb’s chamber work, An Idyll for the Misbegotten, examining the ways in which this musical text sonically evokes post-pastoral sentiments.